Professionals' motivation to support parental self‐management regarding children with physical disability in Dutch rehabilitation services: 'Please mind your gap'. (31st May 2021) - Wong Chung, Ruud; Willemen, Agnes; Voorman, Jeanine; Ketelaar, Marjolijn; Becher, Jules; Schuengel, Carlo
Abstract: Background: Professionals in child healthcare increasingly endorse the support of self‐management in paediatric rehabilitation services for children with physical disability. Less understood though are their views regarding the role of the children's parents, as well as their own role in supporting parents. This study aimed to investigate the motivation of rehabilitation professionals to support self‐management of parents regarding their child with physical disability, professionals' beliefs about parental self‐management, and the perceptions underlying their motivation. Methods: A mixed‐methods strategy was followed using a survey among rehabilitation professionals ( n  = 175) and consecutive semi‐structured interviews ( n  = 16). Associations between autonomous (intrinsic) versus controlled (extrinsic) motivation and beliefs on parental self‐management were tested. For deeper understanding of their motivation, directed content analysis was used to address key themes in the qualitative data extracts. Results: Professionals reported autonomous motivation for parental self‐management support more often than controlled motivation ( t [174] = 29.95, p  < .001). Autonomous motivation was associated with the beliefs about the importance of parental self‐management ( r  = .29, p  < .001). Approximately 90% of the professionals believed that parents should have an active role, though less than 10% considered it important that parents also are independent actors and initiative takers in the rehabilitation process. Interviews revealed that individual professionals struggled with striking a balance between keeping control and 'giving away responsibility' to parents. A 'professional‐like' attitude was expected of parents with 'involvement' and 'commitment' as essential preconditions. Furthermore, professionals expressed the need for additional coaching skills to support parental self‐management. Conclusion: Professionals were predominantly autonomously motivated to support self‐management of parents. However, the dilemmas in giving or taking responsibilities within the partnership with parents may limit their effectiveness in empowering parents. Reflection on the potential gaps between professionals' motivation, beliefs and actual behaviour might be crucial to support parental self‐management.